Nation and social revolution. The thought and action of the young Jordi Solé Tura - Pala, Giaime (Historia y Política, 2019)
Almost ten years after his death, the politician and intellectual Jordi Solé Tura remains very much present in the current Catalan political debate. This is, above all, due to his book Catalanisme i revolució burguesa (1967), the theses of which are often cited in a simplified or distorted manner to confirm or reject positions on the political future of Catalonia. This article proposes a detailed historiographical approach to Solé Tura, based on his early political practice and thought. Thus, on one hand, it studies his affiliation to the Unified Socialist Party of Catalonia (Partit Socialista Unificat de Catalunya), which led to his exile in France and Romania and which ended with his expulsion from the party in 1964. On the other hand, it analyses his writings to demonstrate that Catalanisme i revolució burgesa was clearly based on ideas and concepts developed by Solé between 1956 and 1964.